General Results for General Transmuted-G Distributions (European Journal of Pure and Applied Mathematics, 2021)
In this paper we have given some general results for the general transmuted families of distributions introduced by Rahman et al. (2018a,b). These results are helpful to obtain the results for any member of the general families of distributions and their special cases. We have given some examples for illustration.